دراسة أثر مغنطة مياه الري على مميزات محصول البطاطس - غمام عمارة الجيلاني (سوسة - تونس, 2024)
أجريت تجربة حقلية بمستثمرة فلاحية بمنطقة حاسي خليفة ولاية الوادي اثناء الموسم الزراعي الربيعي على محصول البطاطس بهدف معرفة مدى استجابة خصائص انتاج محصول البطاطس للري بالمياه الممغنطة. نفذت التجربة ضمن تصميم القطاطات العشوائية الكاملة بعاملين للري (ممغنط وغير ممغنط) بواسطة جهاز Delta Water المتحصل عليه من مجمع CPH بقوة مغناطيسية 14500 قاوس، وبثلاث تكرارات مختارة من الحقل ذات ري محوري وقورنت المتوسطات حسب اختبار LSD على مستوى احتمالية 0.05 . بينت النتائج وجود فروق معنوية في متوسط وزن الدرنة والإنتاج في النبات وفي المساحة إضافة الى نسبة الدرنات القياسية وكذلك نسب الدرنات الكبيرة والمتوسطة والصغيرة. وأوضحت النتائج زيادة في عدد الدرنات بالنبات تفوق 20 % ومتوسط وزن الدرنة بنسبة 25% بينما وصلت الزيادة في الإنتاج بنسبة 35%، كما بينت النتائج ان نسبة الدرنات التي تفوق 450غ كانت 10% في معاملة الري الممغنط في حين غياب هذا الحجم في المعاملة الشاهد ، وان نسبة الدرانات الاكبر من 300غ تزيد في معاملة الري الممغنط بنسبة 15%. Abstract: province, during the spring growing season, focusing on potato cultivation. The study aimed to assess the impact of magnetized water irrigation on various aspects of potato crop production. The experiment employed a completely randomized block design, with two irrigation treatments—magnetized and non-magnetized—utilizing the Delta Water device acquired from the CPH complex, delivering water with a magnetic strength of 14500 Gauss. The experiment included three replicates, employing drip irrigation in the selected field plots. Statistical analysis was performed using the LSD test at a significance level of 0.05. The findings revealed significant disparities in average tuber weight, plant yield, and tuber count per unit area, along with variations in the proportions of standard, large, medium, and small tubers. Notably, the results demonstrated a notable increase in tuber count per plant, exceeding 20%, and a substantial 25% rise in average tuber weight, leading to a remarkable 35% boost in overall yield. Furthermore, the magnetized irrigation treatment exhibited a 10% prevalence of tubers exceeding 450g, contrasting with their absence in the control group. Moreover, there was a 15% rise in the occurrence of tubers larger than 300g in plots subjected to magnetized irrigation.
Solanum Tuberosum L بالترب الرملية الصحراوية
Intervention
Keywords: البطاطس; المغنطة; الري; الإنتاج; Potato; Magnetized water; Irrigation; Crop yield